Is Corporate Governance Policy a New Paradigm for Social Responsibility? A Research Agenda from Ghana - Kumaza, Alphonse (Naše gospodarstvo/Our economy, 2019)
Social responsibility has received great authorial comments on making business commitments compensatory for corporate profits and/or rent-seeking in host communities. Unfortunately, that voice remains silent on the fundamental component of business responsibility and its improvement, i.e., governance policy. The paper, consequently, recommends a corporate policy for equitable and compensatory corporate citizenship in local communities.To justify the proposition, three objectives are established: proof that social responsibilities can improve with a governance policy, that authoritative policy represents a crucial change in social initiatives execution, and that policy absence incentivises implementation ineffectiveness and commitments paucity. Triangulation of interviews and survey data through SPSS analysis shows statistically significant coefficients validating the claim that corporate governance policy is an enrichment and facilitator of social responsibilities. The proposed policy framework will not only deliver competitive, scientific, objective, and excellent services but also represent a novel and future academic investigation.